Design and development of self-compacting alkali-activated concrete for energy-efficient building material - Lanjewar, Bhagyashri A.; Kumbalwar, Abhilasha N.; Gavali, Hindavi; Dakwale, Vaidehi A.; Ralegaonkar, Rahul V. (Frontiers in Built Environment, 2025)
Anticipated urbanization and population growth, particularly in developing countries, are expected to boost demand for concrete, resulting in higher emissions and raw material consumption. In response to growing global sustainability awareness, various industries and countries have implemented diverse initiatives aimed at significantly reducing their greenhouse gas emissions. Alkali Activated Concrete (AAC), often known as zero cement concrete, is a viable substitute for conventional concrete. This study developed self-compacting alkali-activated concrete (SCAAC) using agro-industrial wastes and curing at ambient temperatures. The precursors were ground granulated blast furnace slag (GGBS) and fly ash (FA), which were activated with sodium hydroxide flakes and liquid sodium silicate. Co-fired bio-blended ash (BA), an agro-industrial waste, was used to partially replace river sand. The physical, chemical, mineral, and morphological properties of BA were thoroughly investigated. The BA was found suitable to use as a partial replacement for river sand in self-compacting alkali-activated concrete. The curing at ambient temperature was effective in producing a high-strength and durable concrete material. The thermal conductivity of the developed concrete was determined. The reduction in embodied energy for the developed material was calculated. The reduction in peak cooling load was found using computational modeling for cement based concrete and SCAAC. The developed concrete successfully met the specified compressive strength requirement for M30 grade concrete, achieving a value of 38.12 MPa. Reduction in embodied energy (7.37%) of the developed concrete was observed as compared to conventional concrete. Results show that the peak cooling load reduced by 35% compared to conventional concrete [1.9 W/(m.K)] due to the lower thermal conductivity of the developed material [1.247 W/(m.K)]. The use of agro-industrial wastes in the concrete mixture not only reduced the environmental impact but also utilized waste materials that would otherwise be disposed of in landfills. Overall, this study demonstrates the potential for sustainable and environmentally friendly construction materials using agro-industrial wastes.